The Rasch Approach in the Evaluation of Reasoning Instruments for Elementary School Students: A Literature Review - Sri Wulan Dewi; Purwo Susongko; Nuni Widiarti; Arif Widiyatmoko (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to analyze the application of the Rasch Model in evaluating reasoning assessment instruments for elementary school students through a systematic literature review. Reasoning ability is a fundamental component of Higher Order Thinking Skills (HOTS) and plays an important role in developing critical thinking and problem-solving skills. This study employed a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework. Literature was collected from Google Scholar, Scopus, ERIC, and Garuda databases. The review included peer-reviewed journal articles published between 2020 and 2025 that focused on the application of the Rasch Model in educational assessment, reasoning assessment, HOTS, and instrument validation. Following the identification, screening, eligibility, and inclusion stages, 15 articles met the inclusion criteria and were analyzed using thematic content analysis. The findings indicate that the Rasch Model provides more objective, valid, reliable, and stable measurements than Classical Test Theory (CTT). The model effectively evaluates item validity, reliability, item difficulty levels, person-item maps, and item fit statistics, thereby improving the accuracy of reasoning assessment. The study concludes that the Rasch Model is highly relevant for developing HOTS-based reasoning instruments in elementary education and contributes significantly to improving the quality of educational assessment and supporting 21st-century learning evaluation.